Bentuk Tatanan Pemerintahan Dalam Mewujudkan Kesejahteraan Dan Kedamaian Sosial: Strategi Inovasi Pengawasan emerintahan di Daerah Kota Bogor - Rahma Nurhaliza; Miska Salsabila; Ivan Darmawan (Lembaga Pengembangan Kinerja Dosen, 2024)
Government oversight is very important in ensuring accountability and transparency in public administration, especially in the context of regional autonomy. This research examines the challenges and strategies in improving government oversight mechanisms in the City of Bogor, Indonesia. The main findings highlight the importance of strengthening internal oversight institutions such as Regional Inspectorates through capacity building and the use of technology. Innovations such as digital platforms for public participation and performance evaluation systems have been successfully implemented to increase transparency and efficiency in the delivery of public services. However, its implementation overcomes challenges such as limited resources and varying levels of community participation. This research provides further grants from technological advances and a strong regulatory framework to increase the effectiveness of government oversight and reduce the risk of corruption and irregularities in Bogor City government processes.